Multistage honeycomb-shaped and nanoneedle cone composite super-hydrophobic structure and preparation method thereof
By processing multi-stage honeycomb microstructures on the surface of the metal substrate and growing nanoneedle cones, the problem of existing superhydrophobic structures being susceptible to damage in extreme environments is solved, and superhydrophobic effects with high strength, stability and durability are achieved, and an efficient and low-cost preparation method is provided.
Patent Information
- Application Number
- CN202411927621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-14
AI Technical Summary
The existing superhydrophobic structures are susceptible to damage in extreme environments, have weak binding force, poor mechanical stability, and the preparation method has problems such as high equipment requirements, complex operation, long cycle and use of reagents that are harmful to the environment.
A multi-stage honeycomb-shaped and nanoneedle cone composite superhydrophobic structure is adopted. By processing a honeycomb-shaped microstructure on the surface of the metal substrate, and tightly arranged nanoneedle cones are vertically grown inside its structural unit, reducing the actual contact area between the structural surface and water, and improving hydrophobicity and durability.
It is achieved to improve the strength, stability and durability of the superhydrophobic structure while improving the hydrophobicity. The preparation method does not require expensive equipment, has high processing efficiency, low cost and good environmental protection.
Smart Images

Figure CN119615313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material surface modification, and in particular to a multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure and a preparation method thereof. Background Art
[0002] Since the discovery of the lotus effect on super-hydrophobic surfaces was reported, its research in the field of materials science and engineering has attracted much attention. Super-hydrophobic surfaces have shown excellent performance in metal corrosion protection, self-cleaning, anti-icing, and reducing fluid resistance through precise microstructure design and manufacturing. Metal super-hydrophobic surface materials are widely used in the fields of anti-fouling and anti-corrosion of marine ships, self-cleaning and anti-icing of aerospace equipment, and waterproofing of microelectronic components. However, in extreme environments, such as high humidity and salt spray corrosion in marine environments, super-hydrophobic structures have problems such as weak bonding, poor mechanical stability, and easy desorption, and are easily damaged in harsh environments. Therefore, it is urgent to develop super-hydrophobic structures that have both good hydrophobic stability and sufficient strength and durability.
[0003] Existing super-hydrophobic preparation is mainly prepared by electron beam lithography, nanoimprinting, etching, sol-gel method, etc. These preparation methods have the problems of relatively high equipment requirements, complex operation process, difficult to control, long preparation cycle and expensive raw materials. In addition, in the process of preparing super-hydrophobic surface, some reagents that seriously harm the environment, such as strong acid or strong base, are involved. Generally, fluorosilane is selected to reduce the surface energy when modifying the sample, and low surface energy materials such as fluorosilane will bring great pressure to the environment. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide a multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, which can improve the hydrophobicity of the surface of the structure while improving the strength, stability and durability of the super-hydrophobic structure.
[0005] To solve the above problems, the technical solution adopted by the present invention is as follows: a multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, including a honeycomb micron structure processed on the surface of a metal substrate, the honeycomb micron structure includes a plurality of structural units distributed in an array, each of the structural units is distributed with a plurality of nano-needle-cones that grow vertically perpendicular to the metal substrate and are closely arranged; each structural unit of the honeycomb micron structure includes primary hexagonal micron grooves and secondary hexagonal micron grooves distributed in concentric circles, the primary hexagonal micron grooves are located at the periphery of the secondary hexagonal micron grooves, and the primary hexagonal micron grooves and the secondary hexagonal micron grooves are distributed in a stepped manner with high outside and low inside.
[0006] In the above-mentioned multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, the outer diameter of the primary hexagonal micron groove is 100 μm to 500 μm, and the groove depth is 60 μm to 200 μm.
[0007] In the above-mentioned multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, the outer diameter of the secondary hexagonal micron groove is 50 μm to 250 μm, and the groove depth is 60 μm to 200 μm.
[0008] The multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure has a diameter of 50nm to 200nm and a height of 500nm to 10μm.
[0009] The above-mentioned multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure has an array period of structural units of the honeycomb microstructure of 10 μm to 40 μm.
[0010] Compared with the prior art, the beneficial effects of the present invention are: the multi-stage honeycomb and nano-needle cone composite super-hydrophobic structure includes a honeycomb micron structure processed on the surface of the metal substrate, and the honeycomb micron structure has a large number of tiny protrusions, which can effectively reduce the actual contact area between the structure surface and water, thereby reducing the adhesion between the liquid and the solid surface, and helping the water droplets to form highly spherical drops on the structure surface, promoting the rapid rolling of the water droplets on the structure surface, and achieving a good super-hydrophobic effect. At the same time, the multi-stage honeycomb and nano-needle cone composite super-hydrophobic structure is also distributed with a plurality of nano-needle cones vertically growing and closely arranged vertically to the metal substrate inside the structural unit of the honeycomb micron structure, further reducing the actual contact area between the structure surface and water, reducing the surface free energy of the material, further improving the hydrophobicity, and also having good corrosion resistance. Moreover, the honeycomb micron structure, due to its porous surface structure, can be impacted or collided, by deformation and energy absorption to buffer and disperse energy, thereby reducing the impact of external impact on the overall structure, with high strength, good stability and good durability. In addition, the honeycomb microstructure can also provide protection for the nano-needle cones inside it, preventing the nano-needle cones from being worn and broken due to extreme environments, which can further improve the durability of the structure surface.
[0011] The present invention also provides a method for preparing a multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, which is used to prepare the multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, comprising the following steps:
[0012] S1. Select a metal substrate and perform ultrasonic cleaning;
[0013] S2, placing the cleaned and dried metal substrate on the sample stage of the nanosecond laser processing system, and processing a honeycomb micron structure on the surface of the metal substrate using a laser beam;
[0014] S3, placing the laser processed metal substrate in an ultrasonic cleaning machine filled with dilute hydrochloric acid and distilled water to clean it, remove the slag, and then drying it;
[0015] S4, performing electrochemical deposition on the laser processed metal substrate to prepare nano-needle cones inside the structural unit of the honeycomb microstructure;
[0016] S5. The processed metal substrate is placed in an ultrasonic cleaner for cleaning, placed in a high temperature box for drying, and cooled naturally to obtain the desired multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure.
[0017] This preparation method can prepare the above-mentioned multi-level honeycomb and nano-needle cone composite super-hydrophobic structure, so it has at least all the beneficial effects that the above-mentioned multi-level honeycomb and nano-needle cone composite super-hydrophobic structure can bring. In addition, this preparation method uses nanosecond laser "top-down" laser ablation on the metal substrate to process a honeycomb micron structure, and further deposits, modifies and optimizes the rough structure after laser processing through electrochemical deposition technology, forming multiple nano-needle cones that grow vertically perpendicular to the metal substrate and are closely arranged inside the structural unit of the honeycomb micron structure, thereby obtaining the required multi-level honeycomb and nano-needle cone composite super-hydrophobic structure. The above-mentioned manufacturing method does not require expensive equipment, has high processing efficiency, low cost, and good controllability, thereby providing an efficient and low-cost processing method for the firm preparation of highly durable super-hydrophobic surfaces and durable corrosion protection.
[0018] In the method for preparing the multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, in step S1, anhydrous ethanol, pure water and acetone are used to ultrasonically clean the metal substrate respectively, and the cleaning time is 10 minutes to 15 minutes respectively.
[0019] In the preparation method of the above-mentioned multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, in step S2, the output power of each layer of laser processing is 10W~15W, the laser wavelength is 1064nm, the scanning speed is 100mm / s~500mm / s, the scanning spacing is 40μm~60μm, and the number of scans is 3 times~5 times.
[0020] The preparation method of the multi-level honeycomb and nano-needle cone composite super-hydrophobic structure, in step S4, when electrochemical deposition is performed on the metal substrate, the metal substrate is used as the cathode, the nickel block is used as the anode, the deposition solution is NiCl2·6H2O, H3BO3 and inorganic ammonium salt, and the current density is 1A / dm 2 ~6A / dm 2 , the deposition time is 5min~20min.
[0021] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of a composite super-hydrophobic structure according to an embodiment of the present invention;
[0023] Figure 2 is a process flow chart of a preparation method according to an embodiment of the present invention;
[0024] Figure 3 FIG. 1 is a diagram of a laser ablation device according to an embodiment of the present invention, wherein: Figure 3 (a) is a partial schematic diagram of the scanning path of the primary hexagonal micro-grooves. Figure 3 (b) is a partial schematic diagram of the scanning path of the secondary hexagonal micro-grooves;
[0025] Figure 4 Schematic diagram of an electrochemical deposition processing device according to an embodiment of the present invention.
[0026] Explanation of the accompanying drawings: 1-metal substrate, 11-structural unit, 111-primary hexagonal micron groove, 112-secondary hexagonal micron groove, 113-nanocone, 2-sample stage, 3-focusing mirror, 4-plane mirror, 5-lens, 6-laser, 7-computer, 8-plating rack, 9-cathode plate, 10-anode plate, 12 deposition solution, 13 DC power supply. DETAILED DESCRIPTION
[0027] The embodiments of the present invention are described in detail below. Figure 1 The embodiment of the present invention provides a multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, including a honeycomb micron structure processed on the surface of a metal substrate 1, the honeycomb micron structure includes a plurality of structural units 11 distributed in an array, and each structural unit 11 is distributed with a plurality of nano-needle cones 113 that grow vertically perpendicular to the metal substrate and are closely arranged. Each structural unit 11 of the honeycomb micron structure is a tiny pit structure, and the pit structure can be a single groove or a stepped structure composed of multiple concentric grooves. The pit structure has a certain depth, a bottom wall and a side wall, and nano-needle cones 113 grow vertically on the bottom wall and the side wall.
[0028] The multi-stage honeycomb and nano-needle cone composite super-hydrophobic structure includes a honeycomb micron structure processed on the surface of the metal substrate 1. The honeycomb micron structure has a large number of tiny protrusions, which can effectively reduce the actual contact area between the structure surface and water, thereby reducing the adhesion between the liquid and the solid surface, helping water droplets to form highly spherical drops on the structure surface, promoting water droplets to roll quickly on the structure surface, and achieving a good super-hydrophobic effect. At the same time, the multi-stage honeycomb and nano-needle cone composite super-hydrophobic structure is also distributed with a plurality of nano-needle cones 113 that grow vertically perpendicular to the metal substrate and are closely arranged inside the structural unit 11 of the honeycomb micron structure, further reducing the actual contact area between the structure surface and water, reducing the surface free energy of the material, further improving the hydrophobicity, and also having good corrosion resistance. Moreover, the honeycomb micron structure, due to its porous surface structure, can buffer and disperse energy by deformation and energy absorption when it is impacted or collided, thereby reducing the impact of external impact on the overall structure, and has the advantages of high strength, good stability and good durability. In addition, the honeycomb microstructure can also provide protection for the nano-needle cones 113 inside it, preventing the nano-needle cones 113 from being worn and broken due to the influence of extreme environments, and can further improve the durability of the structure surface.
[0029] Furthermore, each structural unit 11 of the honeycomb microstructure includes a primary hexagonal microgroove 111 and a secondary hexagonal microgroove 112 distributed in concentric circles, the primary hexagonal microgroove 111 is located at the periphery of the secondary hexagonal microgroove 112, and the primary hexagonal microgroove 111 and the secondary hexagonal microgroove 112 are distributed in a stepped manner with the outer side being high and the inner side being low. The multi-level honeycomb structure has higher strength and stability, and has higher hydrophobicity and durability. In each structural unit 11, nano-needle cones 113 grow vertically on the side walls and bottom walls of the primary hexagonal microgroove 111 and the secondary hexagonal microgroove 112.
[0030] Furthermore, if Figure 3 As shown in (a), the outer diameter of the primary hexagonal micron groove 111 is 100 μm to 500 μm, the groove depth is 60 μm to 200 μm, and a plurality of primary hexagonal micron grooves 111 are distributed in an array on the surface of the metal substrate 1, and the array period is 10 μm to 40 μm. Figure 3As shown in (b), the outer diameter of the secondary hexagonal micron groove 112 is 50μm to 250μm, the groove depth is 60μm to 200μm, and multiple secondary hexagonal micron grooves 112 are also distributed in an array on the surface of the metal substrate 1, and the array period is 10μm to 40μm, the same as the primary hexagonal micron groove 111. Further, the nano-needle cone 113 can be a nickel needle cone, a copper needle cone, a copper hydroxide needle cone or a zinc oxide nanorod, etc. The diameter of the nano-needle cone 113 is 50nm-200nm, the height is 500nm-10μm, and the height is 80nm to 160nm. The material of the surface of the metal substrate 1 is copper, aluminum alloy or stainless steel, etc.
[0031] Reference Figures 2 to 4 The embodiment of the present invention further provides a method for preparing a multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, which is used to prepare the multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, comprising the following steps:
[0032] S1, selecting a metal substrate 1 and performing ultrasonic cleaning;
[0033] S2, placing the cleaned and dried metal substrate 1 on the sample stage 2 of the nanosecond laser processing system, and processing a honeycomb micron structure on the surface of the metal substrate 1 using a laser beam;
[0034] S3, placing the laser processed metal substrate 1 in an ultrasonic cleaning machine containing dilute hydrochloric acid and distilled water to clean it, remove the slag, and then drying it;
[0035] S4, performing electrochemical deposition on the metal substrate 1 after laser processing, and preparing nano-needle cones 113 inside the structural unit 11 of the honeycomb microstructure;
[0036] S5. The processed metal substrate 1 is placed in an ultrasonic cleaner for cleaning, placed in a high temperature box for drying, and cooled naturally to obtain the desired multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure.
[0037] The preparation method can prepare the above-mentioned multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, so it has at least all the beneficial effects that the above-mentioned multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure can bring. In addition, the preparation method uses nanosecond laser to "top-down" laser ablation on the metal substrate 1 to process a honeycomb micron structure, and further deposits, modifies and optimizes the rough structure after laser processing through electrochemical deposition technology, and forms a plurality of nano-needle cones 113 that grow vertically perpendicular to the metal substrate and are closely arranged inside the structural unit 11 of the honeycomb micron structure, thereby obtaining the desired multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure. The above-mentioned manufacturing method does not require expensive equipment, has high processing efficiency, low cost, and good controllability, thereby providing an efficient and low-cost processing method for the firm preparation of highly durable super-hydrophobic surfaces and durable corrosion protection.
[0038] Furthermore, step S1 specifically includes: selecting a metal substrate 1, grinding and polishing the surface of the metal substrate 1, ultrasonically cleaning the metal substrate 1 with anhydrous ethanol, pure water and acetone respectively, the cleaning time is 10 minutes to 15 minutes respectively, and drying the metal substrate 1 after cleaning.
[0039] Reference Figure 2 and Figure 3 Step S2 specifically includes: before laser processing, draw a scanned image in CAD, and import it into laser software for graphic filling to obtain the corresponding scan path. Figure 3 (a) and (b) are partial enlarged views of the scanning path. Subsequently, a laser ablation device is used to perform laser ablation on the metal substrate 1, such as Figure 3 As shown, the laser ablation device includes a sample stage 2, a focusing mirror 3, a plane mirror 4, a lens 5, a laser 6, and a computer 7. The cleaned and dried metal substrate 1 is placed on the sample stage 2 of the nanosecond laser processing system, and the laser ablation device is controlled by the computer 7. The focusing mirror 3, the plane mirror 4, and the lens 5 are used to focus the laser on the surface of the metal substrate 1, and the layer is selected. Figure 3 (a) Laser ablation is performed on the surface of the metal substrate 1 in the area to be processed to obtain the primary hexagonal micron groove 111. After completion, the layer is switched to Figure 3(b), and ensure that the secondary hexagonal micron groove 112 shown in layer (b) is exactly located at the center of the hexagonal structure in layer (a), and laser ablation is performed again to obtain a stepped multi-level honeycomb structure, in which each structural unit 11 includes an outer higher primary hexagonal micron groove 111 and an inner lower secondary hexagonal micron groove 112. When laser ablation is performed, the output power of each layer processed by the laser is 10W to 15W, the laser wavelength is 1064nm, the scanning speed is 100mm / s to 500mm / s, the scanning spacing is 40μm to 60μm, and the number of scans is 3 to 5 times.
[0040] In step S3, the laser processed metal substrate 1 is placed in an ultrasonic cleaning machine containing dilute hydrochloric acid and distilled water for cleaning for 5 to 10 minutes to remove the slag on the surface of the metal substrate 1, and then dried to obtain Figure 2 The multi-level honeycomb microstructure shown.
[0041] Reference Figure 4 In step S4, an electrochemical deposition treatment device is used, and the electrochemical deposition treatment device includes a treatment tank, a cathode plate 9, an anode plate 10 and a DC power supply 13. The treatment tank is filled with a deposition solution 12. When performing electrochemical deposition treatment, the metal substrate 1 is used as the cathode and the nickel block is used as the anode. The cathode and the anode are placed in the deposition solution 12 respectively using the electroplating rack 8, and the relative distance between the two plates is maintained at 5cm to 8cm. The deposition solution 12 is NiCl2·6H2O, H3BO3 and an inorganic ammonium salt. The NiCl2·6H2O and the nickel block in the deposition solution 12 can continuously provide a stable nickel ion source during the deposition process. The inorganic ammonium salt can stabilize the metal ions, control their release and precipitation during the crystal growth process, and is conducive to directional crystallization. The H3BO3 reagent is used to adjust the pH range of the deposition solution to between 4 and 6. The temperature of the deposition solution 12 is maintained between 55°C and 60°C, and the current density is 1A / dm 2 ~6A / dm 2 , the deposition time is 5min to 20min. Finally, by controlling the current density and deposition time, a plurality of 80nm-160nm nano-needle cone 113 structures that grow vertically and closely arranged perpendicular to the metal substrate are prepared on the surface of the honeycomb structure.
[0042] It should be noted that in the description of the present invention, if there are any orientation descriptions, such as up, down, front, back, left, right, etc., the orientations or positional relationships indicated are all based on the orientations or positional relationships shown in the drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed or operated in a specific orientation, and cannot be understood as a limitation on the present invention.
[0043] In the description of the present invention, "several" means one or more, "more" means two or more, "greater than", "less than", "exceed" etc. are understood to exclude the number itself, and "above", "below", "within" etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used to distinguish the technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0044] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0045] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, characterized in that: The invention comprises a honeycomb micron structure processed on the surface of a metal substrate (1), wherein the honeycomb micron structure comprises a plurality of structural units (11) distributed in an array, wherein each structural unit (11) is provided with a plurality of nano-needle cones (113) vertically growing and closely arranged perpendicular to the metal substrate; each structural unit (11) of the honeycomb micron structure comprises primary hexagonal micron grooves (111) and secondary hexagonal micron grooves (112) distributed in concentric circles, wherein the primary hexagonal micron grooves (111) are located at the periphery of the secondary hexagonal micron grooves (112), and the primary hexagonal micron grooves (111) and the secondary hexagonal micron grooves (112) are distributed in a stepped manner with the outer portion being higher and the inner portion being lower.
2. The multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure according to claim 1, characterized in that: The outer diameter of the primary hexagonal micron groove (111) is 100 μm to 500 μm, and the groove depth is 60 μm to 200 μm.
3. The multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure according to claim 1, characterized in that: The outer diameter of the secondary hexagonal micron groove (112) is 50 μm to 250 μm, and the groove depth is 60 μm to 200 μm.
4. The multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure according to claim 1, characterized in that: The diameter of the nano-needle cone (113) is 50nm-200nm, and the height is 500nm-10μm.
5. The multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure according to claim 1, characterized in that: The array period of the structural unit (11) of the honeycomb microstructure is 10 μm to 40 μm.
6. A method for preparing a multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure, characterized in that: The method for preparing the multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure as claimed in any one of claims 1 to 5 comprises the following steps: S1. Select a metal substrate (1) and perform ultrasonic cleaning; S2, placing the cleaned and dried metal substrate (1) on a sample stage (2) of a nanosecond laser processing system, and processing a honeycomb micron structure on the surface of the metal substrate (1) using a laser beam; S3, placing the laser processed metal substrate (1) in an ultrasonic cleaning machine containing dilute hydrochloric acid and distilled water to clean it, remove the slag, and then drying it; S4, performing electrochemical deposition on the laser-processed metal substrate (1) to prepare nano-needle cones (113) inside the structural unit (11) of the honeycomb microstructure; S5, placing the processed metal substrate (1) in an ultrasonic cleaner for cleaning, placing it in a high temperature box for drying, and cooling it naturally to obtain the desired composite super-hydrophobic structure.
7. The method for preparing the multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure according to claim 6, characterized in that: In step S1, the metal substrate (1) is ultrasonically cleaned using anhydrous ethanol, pure water and acetone, respectively, with the cleaning time being 10 minutes to 15 minutes for each.
8. The method for preparing the multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure according to claim 6, characterized in that: In step S2, the output power of each layer of laser processing is 10W-15W, the laser wavelength is 1064nm, the scanning speed is 100mm / s-500mm / s, the scanning interval is 40μm-60μm, and the number of scans is 3-5 times.
9. The method for preparing the multi-level honeycomb and nano-needle-cone composite super-hydrophobic structure according to claim 6, characterized in that: In step S4, when electrochemical deposition is performed on the metal substrate (1), the metal substrate (1) is used as a cathode, the nickel block is used as an anode, the deposition solution (12) is NiCl2·6H2O, H3BO3 and an inorganic ammonium salt, and the current density is 1A / dm 2 ~6A / dm 2 , the deposition time is 5min~20min.
Citation Information
Cited By
Anti-aging transformer for power transmission and distribution
CN120854119A